2018
DOI: 10.1111/jfs.12540
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex polymerase chain reaction detection of Shiga toxin genes and antibiotic sensitivity of Escherichia coli O157:H7 isolated from beef meat in Quetta, Pakistan

Abstract: The objective of this study was to conduct a qualitative analysis of raw beef meat sold in the city of Quetta, Pakistan for presence and drug sensitivity of the potentially pathogenic Escherichia coli strain O157:H7. The study used 200 raw beef meat samples collected from retail butcher shops. Conventional and rapid biochemical tests, latex agglutination and multiplex polymerase chain reaction (PCR) using primers designed for the rfb O157 and flic H7 genes were used to detect E. coli O157:H7. All O157:H7 isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
1
7
1
Order By: Relevance
“…In our study, three of the O157: H7 isolates tested positive for both of the stx 1 and stx 2 genes, and three tested positive for only stx 2 . This observation is consistent with many other studies that have reported a higher detection of the stx 2 gene than the stx 1 gene in E. coli O157: H7 isolates (Samad, Abbas, Ahmad, Tanveer, et al, 2018). In 800 samples of chicken, beef meat, milk, and vegetables/salads from retail markets in Quetta, the total incidence of E. coli O157: H7 was 8%; in milk, the incidence was 4% from dairy farms and 12% from retail markets (Samad, Abbas, Ahmad, Pokryrshko, & Asmat, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, three of the O157: H7 isolates tested positive for both of the stx 1 and stx 2 genes, and three tested positive for only stx 2 . This observation is consistent with many other studies that have reported a higher detection of the stx 2 gene than the stx 1 gene in E. coli O157: H7 isolates (Samad, Abbas, Ahmad, Tanveer, et al, 2018). In 800 samples of chicken, beef meat, milk, and vegetables/salads from retail markets in Quetta, the total incidence of E. coli O157: H7 was 8%; in milk, the incidence was 4% from dairy farms and 12% from retail markets (Samad, Abbas, Ahmad, Pokryrshko, & Asmat, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Natural reservoirs of E. coli O157: H7 include cattle, sheep, and goats, and the modes of transmission of the infections are animal to person, waterborne, foodborne, and person to person (Samad, Abbas, Ahmad, Tanveer, et al, 2018;Abreham, Teklu, Cox, & Sisay Tessema, 2019;Ateba & Mbewe, 2011;Ferens & Hovde, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although RTE food sold by street vendors is cheap in price, its microbial quality may be compromised if proper hygienic measures are not adopted. In developing countries such as Pakistan, such measures are often neglected, and food items have been reported to be contaminated with several pathogens (Samad et al, 2018a(Samad et al, , b, 2019(Samad et al, , 2020. The results of the present study are alarming, as none of the RTE food samples tested (n = 320) were free of bacteria.…”
Section: Discussioncontrasting
confidence: 53%
“…In the past decades, most attention have been directed toward the use of polymerase chain reaction (PCR) methods of DNA‐based technology. These include single and multiplex PCR with specific primer pairs (Samad et al, 2018), qualitatively real‐time PCR, and loop‐mediated isothermal amplification (LAMP) assays (Zhang et al, 2019) for the detection of E. coli O157:H7 (Liu, Singh, & Mustapha, 2018; Mahmoudzadeh et al, 2016; Suria, Adlin Azlina, Mohd Afendy, & Zamri, 2013). This PCR‐based method is one of the most sensitive and specific methods in routine diagnosis of STES E. coli O157:H7 in foods.…”
Section: The Detection For E Coli O157:h7 In Foodsmentioning
confidence: 99%